Angiotensin‐converting enzyme inhibitors or angiotensin II receptor blockers and prognosis of hypertensive patients hospitalised with COVID‐19. Issue 12 (22nd December 2020) - Covino, Marcello; De Matteis, Giuseppe; Burzo, Maria Livia; Santoro, Michele; Fuorlo, Mariella; Sabia, Luca; Sandroni, Claudio; Gasbarrini, Antonio; Franceschi, Francesco; Gambassi, Giovanni; ,
Abstract: Background: Among hypertensive patients, the association between treatment with angiotensin‐converting enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARB) and the clinical severity of COVID‐19, remains uncertain. Aims: To determine whether hypertensive patients hospitalised with COVID‐19 are at risk of worse outcomes if on treatment with ACEI or ARB compared to other anti‐hypertensive medications. Methods: This is a retrospective study conducted at a single academic medical centre (Fondazione Policlinico A. Gemelli IRCCS, Rome, Italy) from 1 to 31 March 2020. We compared patients on treatment with an ACEI/ARB (ACEI/ARB group) to patients receiving other anti‐hypertensive medications (No‐ACEI/ARB group). The end‐points of the study were the all‐cause in‐hospital death and the combination of in‐hospital death or need for intensive care unit (ICU) admission. Results: The sample included 166 COVID‐19 patients; median age was 74 years and 109 (66%) were men. Overall, 111 (67%) patients were taking an ACEI or ARB. Twenty‐nine (17%) patients died during the hospital stay, and 51 (31%) met the combined end‐point. After adjustment for comorbidities, age and degree of severity at the presentation, ACEI or ARB treatment was an independent predictor neither of in‐hospital death nor of the combination of in‐hospital death/need for ICU. No differences were documented between treatment with ACEI compared to ARB. Conclusions: Among hypertensive patients hospitalised for COVID‐19, treatment with ACEI or ARB is not associated with an increased risk of in‐hospital death.